The Effectiveness of PBL-Role Playing with the TaRL Approach to Improve Student Learning Outcomes and Activity of Number Counting Operations - Rofiqi, Ainur (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Learning mathematics is often considered difficult, scary, and abstract for students at the elementary school level. This has an impact on learning outcomes and students' activeness in mastering material concepts. The PBL-Role Playing model with the TaRL approach is one way to overcome this problem. The purpose of the study is to determine the effectiveness of PBL-role playing learning with the TaRL approach in improving learning outcomes and student activity in numerical counting operation material. This research is classroom action research (CAR). The results showed that the learning completeness in the first cycle was 46.43% and the second cycle was 96.43%. Meanwhile, the results of student activity reached an average of 67.85 in the first cycle and 83.92 in the second cycle. Based on these results, it was concluded that PBL-Role Playing with the TaRL approach was proven to be effective in improving learning outcomes and student activity.